Faktor Yang Mempengaruhi Pengungkapan Sosial: Tekanan Media Sosial Sebagai Variabel Moderasi - Everaldi Oktavian, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to examine the influence of ownership diffusion, independent director, profitability, board diversity, board size, and company size toward CSR disclosure with a moderating effect study from media pressure in manufacturing companies listed in the Indonesian Stock Exchange in the period 2015-2017. The sample was determined by purposive sampling method. The research conducted by taking 64 manufacturing companies. The result of this research shows that ownership diffusion have negative effect on CSR disclosure, while board size, independent director, independent director moderated by media pressure, profitability, and company size have no effect on CSR disclosure